A mouse model with a frameshift mutation in the nuclear factor I/X (NFIX) gene has phenotypic features of Marshall-Smith syndrome - Kooblall, KG; Stevenson, M; Stewart, M; Harris, L; Zalucki, O; Dewhurst, H; Butterfield, N; Leng, H; Hough, TA; Ma, D; Siow, B; Potter, P; et al. (Wiley, 2023)
The nuclear factor I/X (NFIX) gene encodes a ubiquitously expressed transcription factor whose mutations lead to two allelic disorders characterized by developmental, skeletal, and neural abnormalities, namely, Malan syndrome (MAL) and Marshall–Smith syndrome (MSS). NFIX mutations associated with MAL mainly cluster in exon 2 and are cleared by nonsense-mediated decay (NMD) leading to NFIX haploinsufficiency, whereas NFIX mutations associated with MSS are clustered in exons 6–10 and escape NMD and result in the production of dominant-negative mutant NFIX proteins. Thus, different NFIX mutations have distinct consequences on NFIX expression. To elucidate the in vivo effects of MSS-associated NFIX exon 7 mutations, we used CRISPR-Cas9 to generate mouse models with exon 7 deletions that comprised: a frameshift deletion of two nucleotides (Nfix Del2); in-frame deletion of 24 nucleotides (Nfix Del24); and deletion of 140 nucleotides (Nfix Del140). Nfix+/Del2, Nfix+/Del24, Nfix+/Del140, NfixDel24/Del24, and NfixDel140/Del140 mice were viable, normal, and fertile, with no skeletal abnormalities, but NfixDel2/Del2 mice had significantly reduced viability (p < 0.002) and died at 2–3 weeks of age. Nfix Del2 was not cleared by NMD, and NfixDel2/Del2 mice, when compared to Nfix+/+ and Nfix+/Del2 mice, had: growth retardation; short stature with kyphosis; reduced skull length; marked porosity of the vertebrae with decreased vertebral and femoral bone mineral content; and reduced caudal vertebrae height and femur length. Plasma biochemistry analysis revealed NfixDel2/Del2 mice to have increased total alkaline phosphatase activity but decreased C-terminal telopeptide and procollagen-type-1-N-terminal propeptide concentrations compared to Nfix+/+ and Nfix+/Del2 mice. NfixDel2/Del2 mice were also found to have enlarged cerebral cortices and ventricular areas but smaller dentate gyrus compared to Nfix+/+ mice. Thus, NfixDel2/Del2 mice provide a model for studying the in vivo effects of NFIX mutants that escape NMD and result in developmental abnormalities of the skeletal and neural tissues that are associated with MSS.